Supply chain dynamics with assortative matching - Caichun Chai; Eilin Francis; Tiaojun Xiao (University of California, Economics Department, 2016)
This paper studies the evolutionarily stable strategies of one-manufacturer and one-retailer supply chains. Each manufacturer and retailer chooses between two pure strategies of management: shareholder-oriented or stakeholder-oriented. Based on its management strategy, the firm decides its wholesale or retail price. In this paper, we consider supply chains formed by two matching processes: random matching and assortative matching. Our results indicate that random matching does not support interior Nash equilibria; the evolutionarily stable strategy is for both manufacturer and retailer to choose shareholder strategy. We extend Bergstrom (2003) to a two-population game, and compare the dynamics of supply chains under random matching and assortative matching. Interior Nash equilibrium is observed with assortative matching. However, this interior equilibrium is unstable. The four unique strategy profiles obtained by various combinations of the two strategy choices may be evolutionarily stable for certain values of the indices of assortativity.
Keywords: C73; L21; D21; 330; Nash equilibrium; assortative matching; evolutionary stable strategy; replicator equation